A Review on Lipases: Sources, Assays, Immobilization Techniques on Nanomaterials and Applications - Fahim, Yosri A.; El-Khawaga, Ahmed M.; Sallam, Reem M.; Elsayed, Mohamed A.; Assar, Mohamed Farag Ali (BioNanoScience, 2024)
Lipase is a highly utilized enzyme that holds significant value in various biotechnological and industrial applications, such as the food, paper, and oleochemical sectors, as well as in pharmaceutical contexts. Nevertheless, the application of the substance is relatively challenging and costly due to its aqueous solubility and instability. The immobilization technique is frequently employed to enhance the enzymatic activity and stability of lipase, and this approach has demonstrated considerable potential. The performance of immobilized lipase on nanomaterials (NMs) is subject to various factors, including the immobilization mechanisms and the specific type of matrix employed. This review examines recent advancements, mechanisms, and effects of nanomaterials (NMs) on lipase immobilization and activity. We also discuss different methods for lipase activity determination. The potential for multiple applications of immobilized lipases has been taken into consideration.